Timescales of Evidence Evaluation for Decision Making and Associated Confidence Judgments Are Adapted to Task Demands - Harun, Rashed; Jun, Elizabeth; Park, Heui Hye; Ganupuru, Preetham; Goldring, Adam B.; Hanks, Timothy D. (Frontiers in Neuroscience, 2020)
Decision making often involves choosing actions based on relevant evidence. This can benefit from focussing evidence evaluation on the timescale of greatest relevance based on the situation. Here, we use an auditory change detection task to determine how people adjust their timescale of evidence evaluation depending on task demands for detecting changes in their environment and assessing their internal confidence in those decisions. We confirm previous results that people adopt shorter timescales of evidence evaluation for detecting changes in contexts with shorter signal durations, while bolstering those results with model-free analyses not previously used and extending the results to the auditory domain. We also extend these results to show that in contexts with shorter signal durations, people also adopt correspondingly shorter timescales of evidence evaluation for assessing confidence in their decision about detecting a change. These results provide important insights into adaptability and flexible control of evidence evaluation for decision making.